IDH CocoaSoils achievements - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
The CocoaSoils Program is developing and disseminating Integrated Soils Fertlity Management (ISFM) recommendations to smallholder cocoa farmers in Côte d'Ivoire, Cameroon, Ghana, and Nigeria to increase cocoa productivity and avoid deforestation. In the last 4 years, the program has